Exercise training as a novel primary treatment for localised prostate cancer: a multi-site randomised controlled phase II study - L. Bourke (Nature Portfolio, 2018)
Abstract Alternative management strategies for localised prostate cancer are required to reduce morbidity and overtreatment. The aim of this study was to evaluate the feasibility, safety and acceptability of exercise training (ET) with behavioural support as a primary therapy for low/intermediate risk localised prostate cancer. Men with low/intermediate-risk prostate cancer were randomised to 12 months of ET or usual care with physical activity advice (UCwA) in a multi-site open label RCT. Feasibility included acceptability, recruitment, retention, adherence, adverse events and disease progression. Secondary outcomes included quality of life and cardiovascular health indices. Of the 50 men randomised to ET (n = 25) or UCwA (n = 25), 92% (n = 46) completed 12 month assessments. Three men progressed to invasive therapy (two in UCwA). In the ET group, men completed mean: 140 mins per week for 12 months (95% CI 129,152 mins) (94% of target dose) at 75% Hrmax. Men in the ET group demonstrated improved body mass (mean reduction: 2.0 kg; 95% CI −2.9,−1.1), reduced systolic (mean: 13 mmHg; 95%CI 7,19) and diastolic blood pressure (mean:8 mmHg; 95% CI 5,12) and improved quality of life (EQ.5D mean:13 points; 95% CI 7,18). There were no serious adverse events. ET in men with low/intermediate risk prostate cancer is feasible and acceptable with a low progression rate to radical treatment. Early signals on clinically relevant markers were found which warrant further investigation.